PEMODELAN DAN ANALISA YAW-LOCK INPUT MIXER TERHADAP FREE-RUDDER HOVERING MULTICOPTER - Helmy Mukti Himawan; Panji Peksi Branjangan (Jurnal Ilmiah Informatika, 2017)
The main purpose of this research is to compare the response of a modeling and quadcopter implementation when it’s in normal position and given a yaw-lock mixer input with some PID control parameters. Yaw is one of the movable axis parallel to the axis of the earth magnet. The yaw interference comes from the rotor imbalance as the main inertia generator, thus causing a drift effect on yaw. The yaw-lock mixer input system is installed to keep the yaw in one quadcopter heading position as well as the setpoint tracking. One of the advantages of keeping yaw stability is when mounted dolphin 2 fpv camera axis (roll-pitch), with free-rudder image control generated will consist stable. The method used in this research are; the quadcopter is dynamically modeled so that hypotheses can be drawn about the quadcopter response. After obtained the quadcopter response formulation, then do the sampling of magnetometer data. Based on the formulation and the sampling data, a decision was made regarding the control technique that became the yaw-lock mixer input to the quadcopter board. The graphic result of reading control response then analyzed the efficiency and the level of "disturbance cancellation".